Evaluation of antipsychotic utilization among outpatient schizoprenia patients at the mental health facility in West Java - Sutrisno, Entris; Selifiana, Nita; Sodik, Jajang Japar; Fajarrini, Uvika Nurul (Faculty of Pharmacy, Universitas Pancasila, 2025)
Rational use of drugs aims to give therapy according to patient’s clinical needs. Based on Ni komang's research (2021) there are still inaccuracies in the use of antipsychotic drugs. The purpose of this study was to determine the evaluation of the use of Antipsychotics based on the parameters of right indications, drugs, dosage, and frequency in outpatient schizophrenia patients at the West Java Provincial Mental Hospital. The study used a method with descriptive presentation of data and retrospective data collection. Data obtained period October-December 2022 from 130 patients, this study evaluated the use of Antipsychotics with the parameters of right indications, drugs, dosage, and frequency then the data will be analyzed based on the criteria for drug use from Pharmacotherapy A Pathophysiologic Approach 11th and PIONAS. The results of the study on the use of Antipsychotics in schizophrenic patients at the Java Provincial Mental Hospital based on Pharmacotherapy A Pathophysiologic Approach 11th and PIONAS obtained the right indications as much as (100%), the right drugs (100%), the right dose (98%), and the right frequency (98%).